TELEVISION ENDS? CONTRIBUTIONS FROM THE ANALYSIS OF TRANSNATIONAL FOOTBALL AUDIENCES - Balsas, María Soledad (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2019)
With this article, I pursue to problematize the discourses that postulate the end of television by the lights of analysis of transnational football audiences. In particular, in the present work I recover the research experience carried out in the scope of the Napoli Club Buenos Aires. The approach used is the ethnographic one, in its virtual and face-to-face variants. The results indicate the validity of live football as a privileged genre of television reception, especially in the public sphere.